Austrian Elementary School Teachers’ Perception of Professional Challenges During Emergency Distance Teaching due to COVID-19 - Woltran, Flora; Chan, Ralph; Lindner, Katharina-Theresa; Schwab, Susanne (Frontiers in Education, 2021)
Schools around the world have transitioned to emergency distance teaching due to the COVID-19 outbreak. In particular, the first lockdown (in early 2020) came unexpectedly for all actors and stakeholders in Austria. School authorities, parents, students and, above all, teachers were faced with considerable challenges. The aim of the present study is to evaluate the perception of Austrian elementary school teachers about distance teaching during the first lockdown. Using quantitative and qualitative data sets from the Inclusive Home Learning (INCL-LEA) study, the following research question was investigated: what are the main challenges that elementary school teachers faced in distance teaching in Austria due to COVID-19? Triangulation was carried out on mixed methods to answer the research question, and the data were evaluated using the topic analysis method. The teachers identified five greatest challenges: i) a lack of personal contact with the students; ii) additional workload and more stress, iii) non-existent technical equipment; iv) a lack of digital skills; and v) an inability to offer individual support for students at risk. This study has shown that better policies are needed to avoid these problems. Such solutions not only require the purchase of digital devices, but also the development of pedagogically well-thought-out and planned curricula and the provision of opportunities to improve digital skills. Furthermore, it also showed that sustainable working conditions needed to be created to counter the long-term effects of the heavy workload on teachers. However, the difference between distance teaching in times of the pandemic and regular online teaching also needs to be considered when developing and implementing policies.